Profil Protein Trypanosoma evansi dari Daerah Geografis Berbeda di Indonesia Tahun 2012-2014 dengan Sodium Dodecil Sulphate Polyacrylamide Gel Electrophoresis (TRYPANOSOMA EVANSI PROTEIN PROFILE OF DIFFERENT GEOGRAPHICAL AREAS ORIGIN IN INDONESIA - Ekawasti, Fitrine; Yuniarto, Ichwan; Sulinawati, Sulinawati; Subekti, Didik Tulus (Jurnal Veteriner; Vol 18 No 4 (2017), 2018)
Surra outbreak in 2012 has led to more than 1,700 animals have died in the province of East Nusa Tenggara (NTT) Indonesia. Surra case sporadically continues throughout the year in various areas, especially Kalimantan, Banten as well as other areas. Some reports reveal differences in protein profiles among multiple isolates of T. evansi. Therefore the purpose of this research were to find out the protein profile of each isolate T. evansi in Indonesia and the possible biological differences among them. Eleven isolates originating from the province of East Nusa Tenggara, South Kalimantan and Central Kalimantan, Banten, Lampung and Bengkulu has been isolated and purified Using DEAE. Trypanosoma isolate were frezeethawing repeatedly to obtain soluble protein. Furthermore, soluble protein is treated with heating or without heating and then each was run on SDS PAGE with Coomassie Blue staining. The protein profiles of all isolates were compared each other. The results showed that eleven isolates of T. evansi in Indonesia has a very diverse protein profile. Then for the purposes of development of diagnostic kit can be used whole lysate cell (WCL) as stock antigen in serological test process.